The importance of cleanliness in a proper construction site management in malaysia: a contractor’s perspective - Shazwan, M. A.*; Quintin, J. V.*; Osman, N. A. *; Suhaida @ Suhana, Kamarudin Nurul Aini Osman*; Ma’arof, M. I. N.* (IOP Publishing, 2017)
Construction site’s cleanliness and tidiness is one of top main concerns of construction site management. A good site management with adequate planning in regards to housekeeping will ensure safety to both the site’s working personnel and the neighbouring environment. This is especially of priority today due to the rapid growth of construction projects in Malaysia. Nevertheless, to date, statistics had shown that housekeeping related accidents happened repeatedly despite the awareness on site’s cleanliness and tidiness. The objective of this study was to explore constructor’s perspective on site cleanliness and tidiness. A set of questionnaire was distributed to thirty-four (34) Grade 7 CIDB contractors’ firms in Petaling Jaya. Petaling Jaya was chosen since this area are developed area covered with residential area and cleaning management an importance issues. The goals of the survey study were to identify the following items from the perception of the contractors: (i) the hierarchy of importance of several purposes in ensuring construction site’s cleanliness and tidiness, and (ii) the risk factors that influence a construction site’s level of cleanliness and tidiness. It was found that from the contractor’s perspective, ensuring a site cleanliness and tidiness is of importance mainly due to the need in protecting the environment, whilst, the least in cost saving. In addition, poor personnel’s working attitude was found to be the main risk factor that will influences a construction site’s level of cleanliness and tidiness. Conclusively, construction site’s cleanliness and tidiness is highly vital. Even so, for nationwide awareness on the topic matter will requires full cooperation from all related parties.